2003
DOI: 10.1002/nau.10125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of combined electrophysiological and urodynamic recordings to assess sexual disorders in spinal cord injured men

Abstract: Combined neurophysiologic and neurourologic testing provides highly relevant diagnostic informations about sexual dysfunction in men with spinal cord injury. Loss of the BCR and detrusor areflexia imply loss of somatic and parasympathetic reflex activity and correlate with loss of RE. Loss of PE correlates with loss of perineal SSR (sympathetic denervation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 41 publications
0
29
2
3
Order By: Relevance
“…The predominant mode to document the effects of SCI on sexual response in men has been through self-report. 1 Recent research, primarily in females, 2 but also in males with SCIs, 3,4 has used a laboratory-based approach to document the effects of level and degree of SCI on arousal. These studies have shown that the neurologic ability to achieve psychogenic arousal can be predicted in both females 2 and males 5 by the degree of preservation of the combined ability to perceive surface sensation to pinprick and light touch in the T11-L2 dermatomes.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant mode to document the effects of SCI on sexual response in men has been through self-report. 1 Recent research, primarily in females, 2 but also in males with SCIs, 3,4 has used a laboratory-based approach to document the effects of level and degree of SCI on arousal. These studies have shown that the neurologic ability to achieve psychogenic arousal can be predicted in both females 2 and males 5 by the degree of preservation of the combined ability to perceive surface sensation to pinprick and light touch in the T11-L2 dermatomes.…”
Section: Introductionmentioning
confidence: 99%
“…2,11 Despite Significant association between RE and BCR Table 4 The relationship of pSSR with psychogenic erection and psychogenic lubrication…”
Section: Discussionmentioning
confidence: 99%
“…1 Neurophysiological examinations which evaluate distinct divisions of the nervous system such as sympathetic, parasympathetic and somatic nerve fibres, are considered to be crucial especially if they also provide prognostic information. 2,3 Electromyographic examination (EMG) of the pelvic floor muscles is valuable in the assessment of the involvement of the lower sacral segments. Pudendal somatosensory evoked potentials (pSEP) evaluate the afferent pathways arising from genital organs to upper centres, 4 perineal sympathetic skin responses (pSSR) evaluate symphatetic fibres, 5,6 and bulbocavernosus reflex (BCR) recordings evaluate the integrity of sacral reflex arc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of physiological studies to document the effects of SCI on male sexual response has increased. Based on this research, the potential for psychogenic erection is likely related to preservation of sympathetic function to the genitals [3][4]. Until this finding is further documented, psychogenic erection is recommended to be described as present, possible though partially impaired, or absent based on patient report or physiological data, whether available or not ( Table 1).…”
Section: Male Sexual Functionmentioning
confidence: 99%
“…Until this finding is further documented, psychogenic erection is recommended to be described as present, possible though partially impaired, or absent based on patient report or physiological data, whether available or not ( Table 1). Similarly, the potential for reflex erection is apparently based on the presence of reflex function in the sacral level 2 (S2) to S5 spinal segments [3][4]; however, for purposes of the standards, reflex function is recommended to be described as present, possible though partially impaired, or absent. Because ejaculation is most intimately associated with reproductive functioning, it is documented under reproductive function rather than sexual function.…”
Section: Male Sexual Functionmentioning
confidence: 99%